2011
DOI: 10.1007/s10745-011-9398-7
|View full text |Cite
|
Sign up to set email alerts
|

Pastoral Herding Strategies and Governmental Management Objectives: Predation Compensation as a Risk Buffering Strategy in the Saami Reindeer Husbandry

Abstract: Previously it has been found that an important risk buffering strategy in the Saami reindeer husbandry in Norway is the accumulation of large herds of reindeer as this increases long-term household viability. Nevertheless, few studies have investigated how official policies, such as economic compensation for livestock losses, can influence pastoral strategies. This study investigated the effect of received predation compensation on individual husbandry units’ future herd size. The main finding in this study is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…Recent research has suggested that overcompensation for losses due to predation may also be instrumental to herd accumulation, as it may ensure sufficient income at low slaughter intensities (Næss et al . ). Furthermore, in the Norwegian compensation system, large herds pave the way for larger payouts and therefore may hamper the willingness to reduce herd size (Næss et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recent research has suggested that overcompensation for losses due to predation may also be instrumental to herd accumulation, as it may ensure sufficient income at low slaughter intensities (Næss et al . ). Furthermore, in the Norwegian compensation system, large herds pave the way for larger payouts and therefore may hamper the willingness to reduce herd size (Næss et al .…”
Section: Discussionmentioning
confidence: 97%
“…Conversely, it is alleged that claims are generally inflated, and generous compensation for losses has been linked to increased reindeer population growth rates (Næss et al . ) and overabundance on the tundra (Hausner et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the risk-beneficial aspects of having a large herd, this may, however be viewed as a short-term solution that, if followed, decreases long term viability by reducing the insurance potential of large herds. More to the point, official management strategies that fails to incorporate the risk-beneficial aspect of herd accumulation will have a limited effect and may indeed fail entirely [18], [36]. Furthermore, production subsidies alone may not properly account for the decision problem facing herders: how to secure a reliable income while at the same time maximizing long-term survival.…”
Section: Discussionmentioning
confidence: 99%
“…[36], this empirical study is based on governmental statistics compiled and published annually by the Norwegian Reindeer Husbandry Administration. This dataset contains data on herd size (total number of reindeer in the spring per husbandry unit), covering the period 1998–2008 with data from 20 reindeer husbandry summer districts.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation